Agri-food contracts in light of the provisions of new law No 16 of 14 December 2021 to improve the functioning of the food supply chain - Sánchez Hernández, Ángel (Przegląd Prawa Rolnego, 2022)
The imbalances in the food chain due to, among other factors, differences in the bargaining power between agricultural producers and other more powerful operators in the supply chain, lead to the imposition of disadvantageous prices and commercial practices on farmers and breeders (who are the most vulnerable actors in the chain). Law 12/2013 and its successive amendments seek to eliminate these significant imbalances and improve the position of the weaker contractual party (primary producers) in the agri-food chain, thus ensuring farmers and breeders a selling price (determined in a relevant food contract) that will be above the actual production cost, so that they will earn a profit margin allowing them to sustain themselves and continue their agricultural activity.